2021
DOI: 10.3390/ijms22020740
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Modulation, a New Player in the Race against ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal neurodegenerative disease that usually results in respiratory paralysis in an interval of 2 to 4 years. ALS shows a multifactorial pathogenesis with an unknown etiology, and currently lacks an effective treatment. The vast majority of patients exhibit protein aggregation and a dysfunctional mitochondrial accumulation in their motoneurons. As a result, autophagy and mitophagy modulators may be interesting drug candidates that mitigate key pathological hallmarks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 116 publications
0
34
0
Order By: Relevance
“…With advancing age, autophagy gradually subsides and this decline is linked to defective mitochondria and results in inflammaging [189]. Damaged cellular and organelle components that accumulate as a result of inadequate autophagy are released as damage-associated molecular patterns (DAMPs) [190][191][192]. Dysfunctional mitochondria that are not eliminated by mitophagy release large amounts of mitochondrial DNA (mtDNA) into the cytosol and, together with ROS [193,194], metabolites such as ATP, fatty acids, Aβ, succinate, per-oxidized lipids, advanced glycation end-products, altered N-glycans, and HMGB1 are also recognized as DAMPs and trigger an innate immune inflammatory response [195,196] by directly activating TLR9.…”
Section: Defective Autophagy and Neuroinflammationmentioning
confidence: 99%
“…With advancing age, autophagy gradually subsides and this decline is linked to defective mitochondria and results in inflammaging [189]. Damaged cellular and organelle components that accumulate as a result of inadequate autophagy are released as damage-associated molecular patterns (DAMPs) [190][191][192]. Dysfunctional mitochondria that are not eliminated by mitophagy release large amounts of mitochondrial DNA (mtDNA) into the cytosol and, together with ROS [193,194], metabolites such as ATP, fatty acids, Aβ, succinate, per-oxidized lipids, advanced glycation end-products, altered N-glycans, and HMGB1 are also recognized as DAMPs and trigger an innate immune inflammatory response [195,196] by directly activating TLR9.…”
Section: Defective Autophagy and Neuroinflammationmentioning
confidence: 99%
“…The mitochondrial defect that causes energy deficiency in neurons is a major pathological feature of most neurodegenerative diseases and has been extensively reviewed recently (Monzio Compagnoni et al, 2020 ; Yan et al, 2020 ; Goyal and Chaturvedi, 2021 ; Johnson et al, 2021 ; Lee et al, 2021 ; Madruga et al, 2021 ; Nakagawa and Yamada, 2021 ). We have previously reviewed the evidence linking metabolic impairment and mitochondrial defect in neurodegenerative diseases (Liu and Chern, 2015 ; Liu et al, 2017 ).…”
Section: Impaired Translational Control Resulting From Energy Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Recent studies also showed that motor neurons derived from iPSCs of C9orf72 -ALS patients have inferior mitochondrial bioenergetic functions, poor calcium buffering ability, and shorter axons (Dafinca et al, 2020 ; Mehta et al, 2021 ). Collectively, mitochondrial defects and the resultant defective energy metabolism is believed to be a major driver that plays a critical role in ALS pathogenesis and was extensively discussed in recent reviews (Calió et al, 2020 ; Dafinca et al, 2021 ; Jhanji et al, 2021 ; Madruga et al, 2021 ; Nakagawa and Yamada, 2021 ). The possible role of energy deficiency and AMPK activation in the impairment of protein translation in ALS warrants further research.…”
Section: Impaired Translational Control Resulting From Energy Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Accordingly, within the last years, different autophagy modulators, including rapamycin, trehalose or rilmenidine, have been tested. However, they provided mixed results depending on the model used, administration route, and off-target effects ( Madruga et al, 2021 ), highlighting both the complexity and heterogeneity of this disease. Finally, targeting cytosolic Ca 2+ levels might be an additional promising approach, considering the low Ca 2+ buffering capacity and the high risk of glutamate induced excitotoxicity for vulnerable spinal motor neurons innervating fast-twitch muscles.…”
Section: Discussionmentioning
confidence: 99%